(3QSGdI eNJUQI ef cJGH GdQhMs - (3eMeO Hf CHj HcQ Hf CjhH Hf SYO GdRQYj GdOeTbj, CHh YHO Gddg, TeS GdOjf,J (B751 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeg hHYO agPg cQGSI eNJUQI ef cJGH GdQhM dTjN GdESdGe GHf bje GdLhRjI GdeSFdI GdChdi gd JYQa GdCehGJ HRjGQI GdCMjGA hSdGege Ydjge s
(3BNQgG (B:s
(3GdeSFdI GdMGOjI hGdYTQhf hgj gd GdfaS hGMOI hdgG UaGJ hJSei HEYJHGQ cd UaI HGSe hjcajfG bhdg SHMGfg hJYGdi (B:- " (3hjSCdhfc Yf GdQhM bd GdQhM ef CeQ QHi heG ChJjJe ef GdYde ZdG bdjdkG (B" (3hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf L(B2 (3U` (B1421 (3Cf cJGH GdQhM dTeS GdOjf Hf Gdbje GdLhRjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs